Improving the effectiveness and efficiency of outpatient services: a scoping review of interventions at the primary–secondary care interface. (January 2017) - Winpenny, Eleanor M; Miani, Céline; Pitchforth, Emma; King, Sarah; Roland, Martin
Objectives: Variation in patterns of referral from primary care can lead to inappropriate overuse or underuse of specialist resources. Our aim was to review the literature on strategies involving primary care that are designed to improve the effectiveness and efficiency of outpatient services. Methods: A scoping review to update a review published in 2006. We conducted a systematic literature search and qualitative evidence synthesis of studies across five intervention domains: transfer of services from hospital to primary care; relocation of hospital services to primary care; joint working between primary care practitioners and specialists; interventions to change the referral behaviour of primary care practitioners and interventions to change patient behaviour. Results: The 183 studies published since 2005, taken with the findings of the previous review, suggest that transfer of services from secondary to primary care and strategies aimed at changing referral behaviour of primary care clinicians can be effective in reducing outpatient referrals and in increasing the appropriateness of referrals. Availability of specialist advice to primary care practitioners by email or phone and use of store-and-forward telemedicine also show potential for reducing outpatient referrals and hence reducing costs. There was little evidence of a beneficial effect of relocation of specialists to primary care, or joint primary/secondary care management of patients on outpatient referrals. Across all intervention categories there was little evidence available on cost-effectiveness. Conclusions: There are a number of promising interventions which may improve the effectiveness and efficiency of outpatient services, including making it easier for primary care clinicians and specialists to discuss patients by email or phone. There remain substantial gaps in the evidence, particularly on cost-effectiveness, and new interventions should continue to be evaluated as they are implemented more widely. A move for specialists to work in the community is unlikely to be cost-effective without enhancing primary care clinicians' skills through education or joint consultations with complex patients.